THERMAL BEHAVIOUR OF PYROPE AT 1000 AND 1100 °C: MECHANISM OF FE2+ OXIDATION AND DECOMPOSITION MODEL - Zboril R.; Walla J.; Mashlan M.; Barcova K.; Ferrow E.; Martinec P. (My University, 2003)
The mechanism of thermally induced oxidation of Fe2+ from natural pyrope has been studied at 1000 and 1100 C using 57Fe Mssbauer spectroscopy in conjunction with XRD, XRF, AFM, QELS, TG, DTA and electron microprobe analyses. At 1000 C, the non-destructive oxidation of Fe2+ in air includes the partial stabilization of Fe3+ in the dodecahedral 24c position of the garnet structure and the simultaneous formation of hematite particles (15–20 nm). The incorporation of the magnesium ions to the hematite structure results in the suppression of the Morin transition temperature to below 20 K. The general garnet structure is preserved during the redox process at 1000 C, in accordance with XRD and DTA data. At 1100 C, however, oxidative conversion of pyrope to the mixed magnesium aluminium iron oxide, Fe-orthoenstatite and cristoballite was observed. During this destructive decomposition, Fe2+ is predominantly oxidized and incorporated into the spinel structure of Mg(Al,Fe)2O4 and partially stabilized in the structure of orthoenstatite, (Mg,Fe)SiO3. The combination of XRD and Mssbauer data suggest the definite reaction mechanism prevailing, including the refinement of the chemical composition and quantification of the reaction products. The reaction mechanism indicates that the respective distribution of Fe2+and Fe3+ to the enstatite and spinel structures is determined by the total content of Fe2+ in pyrope.
Keywords: Fe-bearing garnet; Mossbauer spectroscopy; Oxidation mechanism; Decomposition products; Alpha Fe2O3